cGMP in mouse rods: the spatiotemporal dynamics underlying single photon responses - Gross, Owen P.; Pugh Jr., Edward N.; Burns, Marie E. (Frontiers in Molecular Neuroscience, 2015)
Vertebrate vision begins when retinal photoreceptors transduce photons into membrane hyperpolarization, which reduces glutamate release onto second-order neurons. In rod photoreceptors, transduction of single photons is achieved by a well-understood G-protein cascade that modulates cGMP levels, and in turn, cGMP-sensitive inward current. The spatial extent and depth of the decline in cGMP during the single photon response have been major issues in phototransduction research since the discovery that single photons elicit substantial and reproducible changes in membrane current. The spatial profile of cGMP decline during the single photon response affects signal gain, and thus may contribute to reduction of trial-to-trial fluctuations in the single photon response. Here we summarize the general principles of rod phototransduction, emphasizing recent advances in resolving the spatiotemporal dynamics of cGMP during the single photon response.